BLACK BANGLE (ZINGIBER OTTENSII VAL.) RHIZOME AND KATUK LEAVES (SAUROPUS ANDROGYNUS L. MERR) EXTRACT COMBINATION PROTECTIVE ROLE ON ADIPOSE TISSUES HISTOLOGIC PROFILE OF HIGH-FAT AND CARBOHYDRATE DIET-INDUCED OBESE MALE RATS - SULAEMAN, AGUS; Patonah; NEGARA, GHINA GRECIA (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The effect of Zingiber ottensii Val. rhizome and Sauropus androgynus L. Merr leaves extract combination was investigated using histologic profile of adipose tissues in obese male rats induced by high-fat and carbohydrate diets. Methods: This was a preventive study, conducted for 42 days by simultaneous administration of diets and extracts administration. The subjects were divided into 8 groups. All groups except negative control group were fed with high-fat and carbohydrate diets. Orlistat, metformin, and curcumin were used as contrast. Result: The phytochemical screening of Z. ottensii Val. rhizome extract showed the presence of flavonoids, saponins, and triterpenoids, meanwhile S. androgynus L. Merr leaves extract presented flavonoids, tannins, saponins, steroids, and triterpenoids. The results showed tissues histological differences in all test group compared with positive control. The most effective combination dose for bangle and katuk leaves extract in protecting adipose tissue was 100 mg/Kg:100 mg/Kg body weight. Conclusion: The combination of black bangle and katuk leaves extract showed a protective role, demonstrated by adipose tissues histologic profile.